Polymorphic behavior of an organic compound - G, Nithya; R, Sudha; Kanakam, Charles C (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Polymorphic crystals were exhibited in many organic compounds. The frequency changes, relative intensities, band contours, and numberof bands were observed in the spectra of different polymorphism which may be due to molecule-molecule interactions in the crystal unit cells. Theshape of a molecule at its site in the unit cell is distorted by molecular interactions. Methods: The identification of a pure crystal form and to quantify a mixture of two forms infrared and Raman spectra of different crystalline formsof the same organic compound can be used. 2'-chloro-4-methoxy-3-nitro benzil (1) was synthesized and its two polymorphic forms were obtainedby recrystallization from the solvents acetone/chloroform and ethanol. The polymorphism present in the compound was confirmed by single crystalX-ray crystallography and differential scanning calorimetry. Results: The polymorph 1.1 crystallizes as triclinic P-1 space group in the solvent acetone – chloroform and the polymorph 1.2 crystallizes asmonoclinic P21/c space group in the solvent ethanol. Discussion: The intermolecular lattice energy and the interplay of molecular conformation in the crystallization and stability of polymorphs areidentified by X-ray crystal structures of conformational polymorphs. Keywords: Conformational polymorphism, Organic compounds, Single crystal growth, X-ray diffraction.